2023
DOI: 10.3389/fpsyg.2023.1144231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a polyphenol-rich grape and blueberry extract (Memophenol™) on cognitive function in older adults with mild cognitive impairment: A randomized, double-blind, placebo-controlled study

Abstract: BackgroundPolyphenols are naturally occurring organic compounds found in plants. Research suggests that their intake reduces the risk of cognitive decline and related dementias. Grapes and blueberries are polyphenol-rich foods that have attracted attention for their potential cognitive-enhancing effects.PurposeExamine the effects of supplementation with a standardized and patented polyphenol-rich grape and blueberry extract (Memophenol™) on cognitive function in older adults with mild cognitive impairment.Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
2
9
3
Order By: Relevance
“…Therefore, it is also possible that elderberry consumption leads to better cerebrovascular parietal function and consequently more cognitive task-related (i.e., visuospatial problem solving, which involves both parietal and frontal regions [38]) neural activation. Finally, unlike previous findings, we did not observe improvement across memory or other aspects of executive function [33]. Other studies have also found improvement in speed of processing as a result of grape/blueberry extract consumption [33,34].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Therefore, it is also possible that elderberry consumption leads to better cerebrovascular parietal function and consequently more cognitive task-related (i.e., visuospatial problem solving, which involves both parietal and frontal regions [38]) neural activation. Finally, unlike previous findings, we did not observe improvement across memory or other aspects of executive function [33]. Other studies have also found improvement in speed of processing as a result of grape/blueberry extract consumption [33,34].…”
Section: Discussioncontrasting
confidence: 99%
“…Our second hypothesis that elderberry juice consumption would lead to greater cognitive improvement than a placebo-control was only partially supported, as we only observed a trend towards greater elderberry improvement in one domain-visuospatial cognitive flexibility. This is in partial agreement with a previous study that found that a blueberry extract improves visuospatial learning in patients with MCI [33]. We offer several potential explanations for the present results.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations